Enhancing EPA Content in an Arctic Diatom: A Factorial Design Study to Evaluate Interactive Effects of Growth Factors - Steinrücken, Pia; Mjøs, Svein A.; Prestegard, Siv K.; Erga, Svein R. (Frontiers in Plant Science, 2018)
Microalgae with a high content of the omega-3 polyunsaturated fatty acids (PUFAs), eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) are of great demand for microalgae-based technologies. An Arctic strain of the diatom Attheya septentrionalis was shown in previous experiments to increase its EPA content from 3.0% to 4.6% of dry weight (DW) in the nutrient-replete exponential phase and nutrient-depleted stationary phase, respectively. In the present study, a factorial-design experiment was used, to investigate this effect in more detail and in combination with varying salinities and irradiances. A mathematical model revealed that both growth phase and salinity, alone and in combination, influenced the EPA content significantly. Maximum EPA values of 7.1% DW were obtained at a salinity of 22 and after five days in stationary phase, and might be related to a decreased silica content, an accumulation of storage lipids containing EPA, or both. However, growth rates were lower for low salinity (0.54 and 0.57 d-1) than high salinity (0.77 and 0.98 d-1) cultures.